Hedonic Evaluation and Chemical Characterization of Catfish Pulpety as an Alternative Animal Protein Food for the Prevention of Stunting in Toddlers Aged 1–3 Years - Kartika Estiani; Suci Ardila; Dika Nurkistin; Muti’ah Maulaya; Muhammad Muayyad Billah (Journal La Medihealtico, 2026)
Inadequate intake of animal protein during critical periods of growth is a major contributor to stunting, while access to high-quality animal protein sources is often constrained by economic limitations. Catfish (Clarias sp.), as an affordable yet nutrient-dense source of animal protein, offers considerable potential for development into an innovative food product aimed at stunting prevention. This study aimed to develop a catfish-based pulpety product as a safe, nutritious, and acceptable alternative source of animal protein for toddlers to support stunting prevention. A quasi-experimental study employing a Completely Randomized Design (CRD) was conducted with 30 untrained panelists. Three pulpety formulations were prepared using different ratios of chicken meat to catfish meat: Formula I (control), Formula II (1:3), and Formula III (1:1). Hedonic testing was performed to evaluate acceptability across the three formulations, followed by chemical composition analysis of the most preferred formula. The results indicated that Formula III was the most favored, providing 214.78 kcal of energy, 5.92 g of protein, 4.54 g of fat, and 10.05 g of carbohydrates per 100 g. Duncan’s multiple range test revealed a statistically significant difference only in the texture parameter (p = 0.004). Overall, the catfish pulpety demonstrated adequate energy, protein, and fat content for stunting prevention, along with acceptable organoleptic properties, highlighting its potential as a functional food alternative for inclusion in national stunting prevention programs.